The effects of long-term Free Air CO2 Enrichment (FACE) on soil aggregation, soil carbon input, and ecosystem CO2 dynamics in a temperate grassland ecosystem - Lenhart, Katharina; Justus Liebig University Giessen (My University, 2008)
Elevated atmospheric CO2 concentrations enhance photosynthesis, however, they also increase respiratory carbon (C) losses from ecosystems. The changes of both will have a yet unknown effect on ecosystem C dynamics and balances. The aim of this study was to investigate the effects of a moderate long-term CO2 enrichment on ecosystem C dynamics of a temperate grassland ecosystem. To address this subject the effects of elevated CO2 on the soil aggregate structure were investigated, and the soil C content and the input of new C to several soil aggregate fractions were determined. Furthermore, the 13C isotope signature of soil air CO2 and ecosystem respiration was measured. The 13C signature was used to separate soil and ecosystem respiration into its autotrophic (plant-derived) and heterotrophic (old soil organic carbon) components. The study was conducted at the Free-Air CO2 Enrichment (FACE) site near Giessen, Germany. The CO2 enrichment started in May 1998 using 13C depleted CO2 with a signature of -25 . In July 2004 the delta13C signature of the enrichment-CO2 was switched from -25 to -48 without altering the CO2 concentration. This experimental setup provided the unique opportunity to trace ecosystem C fluxes without concomitant priming effects of a CO2 step increase.In the Giessen-FACE study no CO2-induced increase in soil aggregation occurred after nine years of elevated CO2. Root biomass increased under [CO2] +30% but remained mainly unaltered in the [CO2] +20% treatment. The CO2 enrichment enhanced ecosystem respiration (Reco) by 13%. However, elevated CO2 did not result in increased soil C sequestration after 9 years of elevated CO2 in any soil aggregate fraction, nor did it prevent the loss of soil C observed between 1998 and 2004 at the site. This C loss coincided with a breakup of large macroaggregates. In the [CO2] +20% enriched plots the input of C to the soil corresponded to 109 ±43.5 g m-2 yr-1 in the first observation period between 1998 and June 2004, and to 44.4 ±32.5 g m-2 yr-1 in the second observation period between June 2004 and June 2006. Under elevated [CO2] +30%, C inputs were 82.1 and 76.2 g m-2 yr-1 for both periods, respectively, indicating no higher C input with increasing [CO2] in both investigation periods.Under elevated [CO2] +20%, the overall contribution of root-derived soil respiration was 55% in the top 15 cm of the soil. The 13C signature of Reco and soil air CO2 showed the strongest depleted values during the growth period, indicating a higher contribution of plant-derived CO2 at that time. The mean contributions of root, leaf and soil respiration to Reco were 29 ±18%, 32 ±23% and 38 ±20%, respectively. A significant decrease in soil air delta 13CO2 with soil depth indicated a relatively higher contribution of root-derived CO2 in the deeper soil layers. The delta13CO2 gradient showed distinct annual dynamics with a significant impact of soil temperature. The steepest delta13CO2 gradients occurred during winter but became less distinctive during the summer month. Overall, the data gave evidence for an accelerated C-turnover with increasing CO2 concentration but without a net C sequestration under elevated CO2. Therefore, we cannot expect grassland ecosystems to reduce the increase in atmospheric CO2 concentration by incorporating part of the additional C into the soil C stocks.

Erhöhte atmosphärische CO2-Konzentrationen steigern die Photosynthese, erhöhen jedoch durch einen Anstieg der Respiration auch den C-Verlust von Ökosystemen. Veränderungen beider Prozesse haben bislang unbekannte Auswirkungen auf die ökosystemaren C-Dynamiken und deren C-Bilanzen. Ziel dieser Arbeit war es daher, die Auswirkungen einer moderaten CO2-Anreicherung auf die Ökosystem C-Dynamik eines temperierten Grünlandökosystems zu untersuchen. Dazu wurden die Effekte von erhöhtem CO2 auf die Aggregatstruktur des Bodens untersucht und der C-Gehalt des Bodens sowie der C-Eintrag in die einzelnen Aggregatklassen ermittelt. Weiterhin wurden die 13C Isotopensignatur von Bodenluft-CO2 und Ökosystematmung gemessen. Anhand der Isotopensignatur wurde die Boden- und Ökosystematmung in ihre autotrophen (pflanzlichen) und heterotrophen (alter organischer Kohlenstoff) Bestandteile unterteilt. Alle Untersuchungen wurden in Rahmen des Giessener Freiland-CO2 Anreicherungsexperiments (Free Air CO2 Enrichment; FACE) in Deutschland durchgeführt. Die CO2-Anreicherung begann bereits im Mai 1998 mit einem 13C-abgereicherten CO2 mit einer Signatur von -25 . Im July 2004 wurde die 13C Signatur des für die Anreicherung verwendeten CO2 s von -25 auf -48 reduziert, ohne jedoch die CO2-Konzentration zu verändern. Im Giessener FACE Experiment konnte nach 9 Jahren unter erhöhtem CO2 keine CO2-induzierte Zunahme der Bodenaggregation beobachtet werden. Zwar zeigte sich eine Zunahme der Wurzelbiomasse unter +30% erhöhtem CO2, die jedoch im Mittel nicht in den um +20% CO2-angereicherten Flächen auftrat. Die CO2-Anreicherung erhöhte die Ökosystematmung (Reco) um 13%. Erhöhtes CO2 führte nach 9 Jahren in den Bodenaggregatfraktionen weder zu einer Zunahme des C-Eintrags, noch verhinderte es den zwischen 1998 und 2004 beobachteten Verlust von Bodenkohlenstoff auf der Versuchsfläche, der mit einem Zerfall der großen Makroaggregate einherging. Unter CO2 +20% betrug der C Eintrag in den Boden 109 ±43.5 g m 2 a 1 während des ersten Untersuchungszeitraumes zwischen 1998 und Juni 2004, und 44.4 ±32.5 g m-2 a-1 während des zweiten Untersuchungszeitraumes zwischen Juni 2004 und Juni 2006. Unter CO2 +30% betrug der C-Eintrag 82.1 und 76.2 g m-2 a-1 für die jeweiligen Zeiträume, was nicht auf einen erhöhten C-Eintrag mit zunehmender CO2-Konzentration und steigender Wurzelbiomasse hindeutet. Unter CO2 + 20% betrug der Anteil des wurzelbürtigen CO2 an der Bodenatmung 55% in den oberen 15 cm. Die 13C Signatur von Reco und Bodenluft-CO2 war während der Wachstumsperiode am negativsten, was auf einen höheren Anteil an pflanzenbürtigem Atmungs-CO2 zu dieser Zeit hindeutet. Die mittleren Anteile von Wurzel-, Blatt- und Bodenatmung an Reco betrugen 29 ±18%, 32 ±23% und 38 ±20%. Eine signifikante Abnahme der delta13CO2 Signatur der Bodenluft mit der Tiefe deutet auf einen höheren Anteil von wurzelbürtigem CO2 in den tieferen Bodenschichten hin. Der delta13C Gradient zeigte eine ausgeprägte jahreszeitliche Dynamik mit signifikantem Einfluss der Bodentemperatur. Die steilsten delta13CO2 Gradienten traten in den Wintermonaten auf, während die Ausprägung in den Sommermonaten nur gering war. Insgesamt belegen die Daten einen schnelleren C-Umsatz mit steigender CO2-Konzentration, jedoch gab es keine zusätzliche C-Einbindung. Daher können wir nicht davon ausgehen, dass Grasslandökosysteme den Anstieg der atmosphärischen CO2-Konzentration reduzieren, indem sie einen Teil des zusätzlichen Kohlenstoffs in den Boden einbinden.
Die Auswirkungen einer Langzeit Freiland CO2 Anreicherung (FACE) auf Bodenaggregation, Bodenkohlenstoffeintrag und ökosystemare CO2 Dynamiken in einem temperierten Grünlandökosystem
Keywords: erhöhtes CO2; 13C; Bodenkohlenstoff; Bodenaggregation; CO2-Dynamiken; elevated CO2; 13C; soil C; soil aggregation; CO2 dynamics; ddc:570